Retired missionaries and faith in a changing society - Gallagher, Carmel (London : Routledge, 2024)
Retired Missionaries and Faith in a Changing Society offers a sociological study of the Irish missionary diaspora. It draws on a series of interviews with female and male Catholic missionaries, mainly nuns and priests, who have worked in Asia, Africa and Central and South America, and who have returned to live in Ireland. The chapters provide unique insight into their experiences, exploring how they have navigated life-course changes in the context of changing church and changing societies. Retired missionaries have several vantage points from which to communicate their understandings, having worked across cultures and encountered some of the most challenging global social problems. Responding to significant changes in the Catholic Church, in Irish society, in their host countries and in mission work itself, their lives offer valuable perspectives on what it is to be Christian in contemporary society.The rich narrative data illuminates deep and complex processes of meaning-making as missionaries have soughtto integrate their religion and spirituality in dynamic and diverse settings. The book suggests that the holistic character of the work of missionaries raises important questions about the different ways of being ethical, religious and acting justly in the world today. It will be of particular interest to scholars of Christianity, missiology, and the sociology of religion.
Introduction1 Irish Catholic Missionaries: Their life course in a changing world and changing Church 2 Missionary focus: What missionaries inherited and how mission evolved3 The missionaries themselves: Pathways to becoming a missionary 4 The missionaries themselves: The realities, challenges and joys of mission life 5 Interculturality 6 Changing Church - what Church?7 Approaches to mission - different ways to serve8 Life stories of retired missionaries: Perspectives for contemporary Irish society and for the Catholic Church Appendix 1 Profile of the missionariesAppendix 2 Participant information sheet
Keywords: Returned missionaries -- Ireland; Catholic Church -- Missions; Catholic Church -- Ireland; RELIGION / Missions & Missionary Work; RELIGION / Christianity / General; SOCIAL SCIENCE / Sociology of Religion